2011
DOI: 10.1097/sla.0b013e3181ff4601
|View full text |Cite
|
Sign up to set email alerts
|

Robotic-Assisted Laparoscopic Anatomic Hepatectomy in China

Abstract: These preliminary results show that robotic-assisted laparoscopic anatomic hepatectomy is safe and feasible with a much lower complication and conversion rate than traditional laparoscopic hepatectomy or open resection. The robotic surgical system may broaden the indications for laparoscopic hepatactomy, and it enabled the surgeon to perform precise laparoscopic liver resection which required hylum dissection, hepatocaval dissection, endoscopic suturing, and microanastamosis. However, more long-term, evidence-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
159
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 173 publications
(167 citation statements)
references
References 30 publications
6
159
1
1
Order By: Relevance
“…No margin was positive. For patients with HCC, the mean surgical margin was 13 mm (range [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], and for colorectal metastases, it was 25 mm (range 5-70) [16]. All these suggest that oncological efficacy can be achieved even in robotic liver resections.…”
Section: Median (Range)mentioning
confidence: 79%
See 3 more Smart Citations
“…No margin was positive. For patients with HCC, the mean surgical margin was 13 mm (range [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], and for colorectal metastases, it was 25 mm (range 5-70) [16]. All these suggest that oncological efficacy can be achieved even in robotic liver resections.…”
Section: Median (Range)mentioning
confidence: 79%
“…Although Giulianotti et al [16] reported that major liver resections are associated with longer operating times (313 vs. 198 min, median) and more blood loss (300 vs. 150 mL, median) when compared with minor resections, there was no difference in mortalities and major morbidities. Anatomical hepatectomies were possible and feasible even in the more challenging posterior segments with the help of the robot [16,17]. Inevitably, it was associated with longer operating time but with similar or lowered blood loss when compared with the laparoscopic group or open group.…”
Section: Median (Range)mentioning
confidence: 98%
See 2 more Smart Citations
“…complications, bile leakage being the most commonly seen (17). Ji et al reported lower complication rates in RAL hepatic surgery compared to laparoscopic and open surgery (7.8% vs. 10% and 12.5% respectively) (22). Yu et al from Korea compared the surgical outcomes of 206 patients who underwent left hemihepatectomy or left lateral sectionectomy via robotic and laparoscopic liver surgery.…”
Section: Robotic Hepatopancreaticobiliary System Surgerymentioning
confidence: 99%